Policy Advocacy on Accessibility of Pedestrian Paths and Trans Padang for People with Disabilities in Padang City - Friend, Andra (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
People with disabilities in Padang City often face discrimination and have difficulty accessing public facilities such as pedestrian paths and public transportation, including Trans Padang. Even though there has been progress in public policy, its implementation is still less than optimal. Advocacy by organizations like PPDI is important to ensure their rights are fulfilled. This research analyzes accessibility policy advocacy in Padang using descriptive qualitative methods. Data was collected through interviews and documentation studies, tested by data triangulation. The results show that advocacy is going well but is hampered by the completeness of the files. The response from the relevant agencies was positive. Supporting factors include community involvement, effective communication, policy understanding, commitment, policy maker support, collaborative approach, and media involvement. Inhibiting factors include data collection, lack of resources, and public indifference.